2021
DOI: 10.1080/15299732.2020.1869650
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Hippocampal and Amygdala Volumes in Patients Diagnosed With Dissociative Identity Disorder

Abstract: Dissociative Identity Disorder (DID), an illness characterized by multiple personality states, has long been a controversial diagnosis within the psychiatric community. Demonstrating a neuroanatomical basis for the disorder may help to resolve the controversy. Current literature on the neuroanatomy associated with DID has focused on the hippocampus and amygdala and are inconclusive. This meta-analysis pools the results from n = 3 studies to compare the mean size of these two structures between DID patients, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Topics within the empirical articles included clinical features (28%), assessment (17%), etiology (17%), comorbidity (17%), cognitive features (8%), and treatment (7%). Among the 18 etiology articles, the biological approach was most common (Blihar et al, 2021;Campone, 2014;Dimitrova et al, 2023;Reinders et al, 2014;Schlumpf et al, 2014;Weniger et al, 2013), followed by the trauma model, although these articles often included biological components as well (Chalavi et al, 2015a(Chalavi et al, , 2015bDorahy et al, 2016;Krüger and Fletcher, 2017). Several articles directly compared the ability of multiple models of etiology to explain the results.…”
Section: Research Topicsmentioning
confidence: 99%
“…Topics within the empirical articles included clinical features (28%), assessment (17%), etiology (17%), comorbidity (17%), cognitive features (8%), and treatment (7%). Among the 18 etiology articles, the biological approach was most common (Blihar et al, 2021;Campone, 2014;Dimitrova et al, 2023;Reinders et al, 2014;Schlumpf et al, 2014;Weniger et al, 2013), followed by the trauma model, although these articles often included biological components as well (Chalavi et al, 2015a(Chalavi et al, , 2015bDorahy et al, 2016;Krüger and Fletcher, 2017). Several articles directly compared the ability of multiple models of etiology to explain the results.…”
Section: Research Topicsmentioning
confidence: 99%
“…A meta-analysis showed that changes in amygdala and hippocampal volume in DID patients on magnetic resonance imaging (MRI) were similar to those with PTSD [27]. This is because the work of the limbic system affects human emotions which work more actively in DID patients [28].…”
Section: Pathophysiology Of Didmentioning
confidence: 99%